1987
DOI: 10.1136/jcp.40.12.1397
|View full text |Cite
|
Sign up to set email alerts
|

Association between production of toxins A and B and types of Clostridium difficile.

Abstract: SUMMARY One hundred and seventy two strains of Clostridium difficile isolated from 62 patients with antibiotic associated diarrhoea or pseudomembranous colitis were analysed for the production of toxins A and B and typed using "5S-methionine labelling followed by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). There was a correlation between production of toxins A and B and the type of C difficile. One hundred and forty four of 172 strains were either high or low producers of both toxins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…It is thus of interest to note that the same EP type has been responsible for outbreaks of infection on two continents. This is clearly an area for further study but it does lend support to the suggestions of others that there rnay be strain-specific differences in virulence [6][7][8][9] and that specific types are associated with major outbreaks [7,12,16]. In the Canadian study, more electrophoretypes (17) were found to be present in the hospital than in the Manchester group (5) and EP type 1 accounted for a lower proportion of the total isolates examined in the former.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is thus of interest to note that the same EP type has been responsible for outbreaks of infection on two continents. This is clearly an area for further study but it does lend support to the suggestions of others that there rnay be strain-specific differences in virulence [6][7][8][9] and that specific types are associated with major outbreaks [7,12,16]. In the Canadian study, more electrophoretypes (17) were found to be present in the hospital than in the Manchester group (5) and EP type 1 accounted for a lower proportion of the total isolates examined in the former.…”
Section: Discussionsupporting
confidence: 68%
“…Although these may provide the organism with much of its pathogenic potential, the spectrum and severity of clinical presentations associated with the organism may be because of variance between strains in their I12 intrinsic ability to cause disease. A number of clinical studies also support the possibility of strain-specific differences in virulence [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This is most probably due to the amount of toxins produced (Wren et al, 1987). Some strains were reported to be deficient in TcdA production while still producing TcdB (Torres, 1991).…”
Section: Abbreviations Cddl-4 Clostridium Difficilementioning
confidence: 99%
“…'~-'~ Some serogroups are homogeneous with regard to toxin production but others include toxigenic and non-toxigenic strains. 8 All strains of serogroup F produced cytotoxin, but toxin A production was not determined. 15 Strains from this serogroup were mainly isolated from asymptomatic infants.…”
Section: Introductionmentioning
confidence: 99%